Successful Treatment of Refractory Generalized Granuloma Annulare with Upadacitinib - Alexis Coican; Abigail Meckley; Nathan Sagasser; Melinda Greenfield; Eingun James Song; Jessica El-Bahri (Hindawi Limited, 2024)
Granuloma annulare is a poorly understood dermatosis that, when generalized, can occur in up to 15 percent of patients. In these cases, treatment is frustrating and experimental. We report a case of a 60-year-old woman and a 41-year-old woman who demonstrated resolution of recalcitrant, generalized granuloma annulare (GA) following oral treatment with upadacitinib. After showing little to no response to other various treatments, such as steroids, antibiotic regimens, and systemic therapies, each patient was started on 15 mg of daily upadacitinib. At 2 months, one patient had complete clearance of all lesions while the other patient experienced noticeable improvement. Within 4 months, the other patient reached total resolution of her lesions. These cases provide evidence of a therapeutic option that may shorten disease duration and provide relief from cutaneous disease.